Kualitas Bakteriologi (Fecal Coliform) Mata Air Desa Toobaun Kabupaten Kupang - Sarifan, Gracyana Putri; Semiun, Chatarina Gradict; Mamulak, Yulita Iryani (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2025)
Springs are groundwater that comes out on its own to the surface of the earth. Water sources originating from springs are generally suitable for direct consumption because they undergo natural purification. However, the high demand for clean water causes springs to experience anthropogenic pressure, which can reduce the quality of spring water. The study aimed to determine the Bacteriological quality of spring water in Toobaun village. The method used in this study was the Most Probable Number (MPN), using a series of five tubes with a variety of 5-5-5. The test included three stages, namely the prediction test, the confirmation test, and the complete test. The data obtained were presented in the form of a table, then compared with the MPN table value and analyzed descriptively by comparing the MPN value with the water quality standard, namely PP No. 22 of 2021 (class I). The results of the study showed that the Fecal Coliform value found was 220 MPN/100ml and did not meet the quality standards of PP No. 22 of 2021 (Class I). In the complete test using EMBA media, three types of bacteria were found that had characteristics similar to Escherichia coli and Salmonella sp. Klebsiella sp. Based on the results of water testing at the Toobaun spring, it cannot be consumed directly without first being processed.